2022
DOI: 10.3390/su14074075
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Self-Regulated Learning for Students in Underdeveloped Areas: The Case of Indonesia Nationwide Online-Learning Program

Abstract: The COVID-19 pandemic has caused educators around the world to access online-learning systems. Applying the online system involves challenges, such as the students’ need to cope with changes in their learning process, where they must develop capabilities to manage their learning more independently. Self-Regulated Learning (SRL) is an approach considered to help us understand students’ ability to manage their learning strategies and achieve improved performance. This paper aims to investigate the SRL of Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…And finally, the model is evaluated after iterations of the model for validation and the pre-trained model is an ensemble of the training and testing data. The exploratory data analysis module, data identification, and data preparation parts of the methods are done separately [36]. The appropriate pipeline of data processing is carried out in the Python framework to convert the legacy data and the primary form of data to the labelled data where the feature encoding is done in the pipeline.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…And finally, the model is evaluated after iterations of the model for validation and the pre-trained model is an ensemble of the training and testing data. The exploratory data analysis module, data identification, and data preparation parts of the methods are done separately [36]. The appropriate pipeline of data processing is carried out in the Python framework to convert the legacy data and the primary form of data to the labelled data where the feature encoding is done in the pipeline.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The penultimate group consists of studies that explicitly discuss the impact of modern technology on the self-regulation of learning, whether it is Serious Game (Ocampo, 2017), SPADA (Rizki et al , 2022), ePortfolio (Alexiou and Paraskeva, 2019, 2020) or FC (Blau and Shamir-Inbal, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Cao et al (2022) used CSD to reveal the temporal management of SRL. In contrast, Rizki et al (2022) work with SPADA uses CSD, which helps teachers to observe students' learning behavior patterns in real time. SPADA is one of the LMS.…”
Section: Study Selection For Analysismentioning
confidence: 99%
“…Past Studies on Self-Regulated Learning Numerous studies have discovered self-regulated learning in various learning contexts. For example, Rizki et al (2022) explored the adaptation of self-regulated learning with the use of modern technology in Indonesia's higher education systems during the spread of virus Covid 19. The study was conducted to identify the effectiveness of the learning management system (LMS) as a self-regulated learning tool, which is called SPADA that has been enforced by the government.…”
Section: Past Studies On Motivation For Learningmentioning
confidence: 99%
“…However, the results also found that the students have minimum social learning while learning in an online method. Therefore, the study has recommended some improvements on the SPADA's platform architecture to ensure the system can enhance and support the student's engagement in their online learning process (Rizki et al, 2022). Additionally, other than higher education institutions, self-regulated learning is also applicable for elementary school students.…”
Section: Past Studies On Motivation For Learningmentioning
confidence: 99%